2019
DOI: 10.3390/ijerph16152727
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Elemental Contaminants in Unregulated Water across Western Navajo Nation

Abstract: The geologic profile of the western United States lends itself to naturally elevated levels of arsenic and uranium in groundwater and can be exacerbated by mining enterprises. The Navajo Nation, located in the American Southwest, is the largest contiguous Native American Nation and has over a 100-year legacy of hard rock mining. This study has two objectives, quantify the arsenic and uranium concentrations in water systems in the Arizona and Utah side of the Navajo Nation compared to the New Mexico side and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 49 publications
1
44
0
Order By: Relevance
“…Contamination of groundwater from U mining can occur due to erosion of tailing piles and from open pit mining below the water table that produce mine waste water (US EPA 2007). Through increased exposure to water and oxygen, mining activities increase the mobilization of elements such as U and arsenic (As); therefore, the risk of contamination of natural water sources is greater in mining areas (Hoover et al 2017; Credo et al 2019). Arsenic is a natural occurring contaminant that is elevated in groundwater in the southwestern United States due in part to desorption reactions with metal oxides, dissolution reactions, a concentration effect due to high evaporation rates in arid zones, and mining activity (Smedley and Kinniburgh 2002).…”
mentioning
confidence: 99%
“…Contamination of groundwater from U mining can occur due to erosion of tailing piles and from open pit mining below the water table that produce mine waste water (US EPA 2007). Through increased exposure to water and oxygen, mining activities increase the mobilization of elements such as U and arsenic (As); therefore, the risk of contamination of natural water sources is greater in mining areas (Hoover et al 2017; Credo et al 2019). Arsenic is a natural occurring contaminant that is elevated in groundwater in the southwestern United States due in part to desorption reactions with metal oxides, dissolution reactions, a concentration effect due to high evaporation rates in arid zones, and mining activity (Smedley and Kinniburgh 2002).…”
mentioning
confidence: 99%
“…[20] On the Navajo Nation, it is reported that 30% of the community consumes unsafe water that is intended for livestock only or has unregulated water sources for drinking purposes. [21] Multiple studies have found elevated levels of metal(loid)s, such as arsenic, cadmium, lead, vanadium, manganese, and uranium on Diné lands, [22][23][24][25][26][27][28] and in human drinking water sources in communities that rely on water for ingestion, cleaning, agriculture, animal husbandry, and cultural needs. [29] Hard rock mining and its' toxicants are only one example, as environmental contamination may occur from other industries (i.e., gas, coal, oil).…”
Section: Watermentioning
confidence: 99%
“…Inductively coupled plasma mass spectrometry (adapted from Credo et al 2019) For this study, arsenic levels were quantified at only one time point for each site. We collected two 500 ml water samples from each of the three sites on December 4, 2019 in clean wide-mouth packers (#05-719-149B, Fisher After reduction of arsenate (iAs V ) into arsenite (iAs III ), it is metabolized to monomethylarsonic acid (MMA III or MMA V ) and subsequently to dimethylarsinic acid (DMA III or DMA V ), a less toxic chemical, via methylation by arsenite (+3) methyltransferase (as3mt) and oxidation.…”
Section: Collecting Sitesmentioning
confidence: 99%